TUBERCULOUS MENINGOENCEPHALITIS MASKING MYXOEDEMA COMA - Naidu, Thaalitha; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Myxoedema coma is a rare but potentially lethal complication of extreme hypothyroidism. Despite its low incidence, the mortality rate may reach 60%. CASE A 40-year-old male presented with shortness of breath, vomiting, frontal headache and abnormal behaviour for 2 days. He also suffered from fever, chesty cough, and chronic back pain for 2 weeks. He was confused, had unequal pupils, loss of lateral 1/3rd of his eyebrows, and reduced breath sounds bilaterally. Cranial CT scan demonstrated obstructive hydrocephalus necessitating external ventricular drainage. Pus aspirated from a right exudative pleural effusion yielded an ADA value of 68.78U/L. An MRI showed intracranial hyperintense lesions and L3/L4 spondylitis. Diagnosed with disseminated TB, anti-TB treatment with tapering doses of dexamethasone was commenced. He needed tracheostomy for prolonged intubation and had poor GCS recovery. On day 28 of hospitalization, he developed hypotension with a BP of 70/50 mm Hg, warranting noradrenaline infusion. In retrospect, he had been bradycardic (heart rate ranged 30-55 bpm), hypothermic with a temperature of 35.7°C, and had recurrent hypoglycaemic episodes 7 days prior. Blood gas demonstrated CO2 retention. Echocardiography did not exhibit pericardial effusion. His TSH level was >48.8 m IU/L, T4 level <3.2 pmol/L, and morning cortisol 163 nmol/L. He was administered IV Hydrocortisone 100 mg including IV Thyroxine 200mcg slow bolus. IV Thyroxine was then reduced to 100 mcg OD for 2 days and subsequently switched to an oral maintenance dose of 100 mcg OD. His heart rate along with his temperature normalized. He was eventually weaned off inotropic support. Repeat TFTs after 6 days showed T4 of 11.1 pmol/L and TSH of 9 m IU/L. CONCLUSION In this case, the presence of TB meningoencephalitis obscured the diagnosis of severe hypothyroidism, resulting in treatment delay. In cases with high clinical suspicion of myxoedema coma, stress doses of hydrocortisone and thyroxine replacement are vital even prior to laboratory confirmation to enhance survival.